Study on the Management Model of Madrasah Diniyah Takmiliyah in Demak Regency: Implementation and Benefits - Manijo, Manijo; Firdiansyah, Bahtiar; Nisa, Fariq Fahrun (Al Hikmah: Journal of Education, 2024)
The management of Madrasah Diniyah Takmiliyah is hampered by a lack of management professionalism, limited resources, and innovation according to the times. The research aims to identify the management model, application and benefits obtained from the management model of Madrasah Diniyah Takniliyah in Demak Regency. The research uses a qualitative approach of field research methods, utilizing interviews, observations, and documentation as data collection techniques. The analysis was carried out by referring to the concept of madrasah management according to Dedy Mulyasa and Rohiat. The results of the research include three aspects, the management model of Madrasah Diniyah Takmiliyah in Demak which is unique and based on local culture with the concept of trilogy; implementation of management models under PC RMI-NU and PC FKDT; as well as benefits that include strengthening religious education, community empowerment, and character building for the younger generation. This research contributes to the development of Islamic education management literature, as well as provides recommendations to improve the management of Madrasah Diniyah Takmiliyah in other regions.